Deficiency of migration inhibitory factor influences the gut microbiota of C57BL/6 mice infected with Plasmodium berghei ANKA - Xie, Yiting; Guan, Wei; Zhao, Yanqing; Yan, Siyi; Guo, Kun; Chen, Sirui; Hu, Xinyi; Shi, Haimei; Li, Jian (Frontiers in Microbiology, 2022)
Cerebral malaria (CM), as one of the most common complications in severe malaria, has threatened millions of individuals’ neurological health and even their lives. Macrophage migration inhibitory factor (MIF), a pleiotropic proinflammatory factor in humans, seems to be a risk factor for death in patients with CM, but its functional mechanism remains unclear. To verify whether affecting the intestinal microbes of the host was one of the mechanisms by which MIF regulates CM, C57BL/6 mice, including WT + PbA, MIF-KO + PbA and their uninfected controls, were sent for 16S rRNA-based sequencing targeting the V4 region of the intestinal microbiota through the Illumina MiSeq platform. The results showed that OTU clustering, alpha and beta diversity in the four groups involved had evident variation. The relative abundance at different taxonomic levels, especially the dominant intestinal flora, was obviously changed. The LEfSe analysis screened out several biomarkers, including significantly reduced Ligilactobacillus (Lactobacillus murinus) in WPbA mice compared to the WT group and Akkermansia (Akkermansia_muciniphila) in KPbA mice compared to the WPbA group. For MIF KO groups, mice infected with PbA or uninfected showed significant enrichment of producers of short-chain fatty acids, including Dubosiella and Faecalibaculum (Faecalibaculum rodentium) in KPbA, and Lachnospiraceae_NK4A136_group and Firmicutes_bacterium_M10-2 in KO. This study not only further proved the gut microbiota changes in C57BL/6 mice caused by PbA infection, but also found that MIF deletion directly affected the changes in the gut microbiota of C57BL/6 mice before and after PbA infection. This finding reveals a potential mechanism by which MIF regulates CM. Combining MIF with potential microbial biomarkers will provide a promising idea to develop combined drugs for improving CM in the future.